Associativity and organizational culture of hass avocado production chains in the huancavelica region, Peru 2003−2019 - Camac, Giomara (2021)
The objective of the research was to determine the relationship between associativity and the organizational culture of Hass avocado production chains in the Huancavelica Region, Peru in the period 2003–2019. The research is of an applied type, the inductive inferential scientific method was applied. Likewise, the research design used is non-experimental, cross-sectional. A questionnaire was applied to 105 Hass avocado producers from the Huancavelica Region, one of the poorest regions of Peru, in the middle basin of the Mantaro River Valley from the Mariscal Caceres district to the Mantacra town center. In the study, it was found that the associativity environment (ENT) (ASO), based on organizational culture (COR), has a significant influence on the communication dimension (p < 0.05). Regarding support services (SA), has a significant influence on the quality dimension (p < 0.05). Also in relationships (REL), they have a significant influence on the communication and adaptability dimensions (p < 0.05). Finally, in government policies (GP), it has a significant relationship with the communication dimension (p < 0.05). Therefore, these dimensions generate a positive impact on organizational culture.